DIGITAL TRANSFORMATION IN RETAIL BUSINESS - Sandra Mrvica MAĐARAC; Marko ELJUGA; Zvonimir FILIPOVIĆ (Challenges of the Knowledge Society)
The way of doing retail business and its form has changed substantially during the course of the last 20 years or so. Under the influence of technology, new retail forms have emerged, as well as the new ways of doing business. Modern retail uses advanced tools in sales processes, all for the purpose to make it easier for customers and to speed up the sales process. The objectives of the digital retail transformation are: the increase of efficiency of sales, time savings when purchasing, costs reductions and higher level of organization and productivity. As a complex marketing strategy, instore technology is changing retail business, and it has become an integral part of modern retail logistics. By providing digitalised services to customers through their integration, digital retail tools contribute to major changes in the trading business. Trading companies are forced to keep up with the social habits and modern technological tools. By implementation of new technological solutions in retail, to customers are offered simpler and more modern ways of selling. However, it is the customers who decide on the use of these tools in retail, so it is necessary for trade companies to listen to the habits of customers. In the paper are explored and analysed some of the examples of a retail digital transformation, such as: using of QR codes, buying when using the augmented reality (A-commerce), trade without cash desks and sellers, purchase by means of use of virtual googles, purchase when using virtual assistants, or by omnichannel. There are also some of the examples of trading companies that successfully use these sales tools.